2012
DOI: 10.4049/jimmunol.1102711
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B27 Homodimers and Free H Chains Are Stronger Ligands for Leukocyte Ig-like Receptor B2 than Classical HLA Class I

Abstract: Possession of HLA-B27 (B27), strongly predisposes to the development of spondyloarthritis. B27 forms classical heterotrimeric complexes with beta-2-microglobulin (β2m) and peptide, and (β2m–free) free H chain (FHC) forms including B27 dimers (termed B272) at the cell surface. In this study we characterise the interaction of HLA-B27 with LILR, leukocyte Ig-like receptor (LILR)B1 and LILRB2 biophysically, biochemically and by FACS staining. LILRB1 bound to B27 heterotrimers with a KD of 5.3 ±1.5 μM but did not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 26 publications
1
43
0
Order By: Relevance
“…The HLA-B*27:05 plasmid was constructed using a previously described PHR-SIN lentiviral vector (22). This plasmid was used to transduce HeLa and mFib cells.…”
Section: Methodsmentioning
confidence: 99%
“…The HLA-B*27:05 plasmid was constructed using a previously described PHR-SIN lentiviral vector (22). This plasmid was used to transduce HeLa and mFib cells.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, HLA-G displays a unique Cys42 residue, allowing the formation of disulphide-linked dimers, which were shown to establish a high-affinity interaction with LILRB1 [15][16][17]. HLA-B27 β2m-free heavy chains (FHC) dimerizing through Cys67, efficiently interacted with LILRB2 [18].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, HLA-G displays a unique Cys42 residue, allowing the formation of disulphide-linked dimers, which were shown to establish a high-affinity interaction with LILRB1 [15][16][17]. HLA-B27 β2m-free heavy chains (FHC) dimerizing through Cys67, efficiently interacted with LILRB2 [18].HLA-B7 cytoplasmic Cys residues were shown to play a crucial role in LILRB1 recognition [19]; moreover, Cys325 and Cys339 were reported to be respectively involved in the formation of β2m-associated HLA-B27 and -A2 dimers in exosomes [20,21].Altogether, these observations suggest that these noncanonical HLA class Ia conformers might enhance the interaction with LILRB1. In the present study experimental evidence supporting this hypothesis is provided.…”
mentioning
confidence: 99%
“…Rudwaleit et al (2001) found that T cells producing TNF-α and IFN-γ are decreased in healthy controls both HLA-B27+ and HLA-B27-compared to HLA-B27+ AS patients [59]. Another interesting property of HLA-B27 is that β2-microglobulin free heavy chains of HLA-B27 were shown to interact with killer cell immunoglobulin-like receptor 3DL2 (KIR3DL2) and leucocyte immunoglobulin-like receptor B2 (LILRB2) with a higher affinity than heteromeric HLA-B27-β2-microglobulins in patients with spondyloarthropathies [60,61].…”
Section: Clinical Relation Of Hla-b27 and Asmentioning
confidence: 99%